Stroma cell priming in enteric lymphoid organ morphogenesis - Ferreira, Manuela; Domingues, Rita G.; Veiga-Fernandes, Henrique (Frontiers in Immunology, 2012)
The lymphoid system is equipped with a network of specialized platforms located at strategic sites, which grant strict immune-surveillance and efficient immune responses. The development of these peripheral secondary lymphoid organs occurs mainly in utero, while tertiary lymphoid structures can form in adulthood generally in response to persistent infection and inflammation. Regardless of the lymphoid tissue and intrinsic cellular and molecular differences, it is now well established that the recruitment of fully functional Lymphoid Tissue inducer (LTi) cells to presumptive lymphoid organ sites, and their consequent close and reciprocal interaction with resident stroma cells, are central to secondary lymphoid organ formation. In contrast, the nature of events that initially prime resident sessile stroma cells to recruit and retain LTi cells remains poorly understood.